Platelet reactivity and bleeding outcomes in female patients presenting with ST-segment elevation myocardial infarction: a COMPARE CRUSH substudy. (14th October 2021) - Vogel, R F; Vlachojannis, G J; Wilschut, J M; Lemmert, M E; Diletti, R; Nuis, R J; Paradies, V; Alexopoulos, D; Zijlstra, F; Montalescot, G; Angiolillo, D J; Krucoff, M W; et al.
Abstract: Background/Introduction: Females presenting with ST-segment elevation myocardial infarction (STEMI) are characterized by an increased risk of bleeding after primary percutaneous coronary intervention (pPCI) compared with males. The reason for increased bleeding rates is multifactorial, including age, comorbidities, vessel anatomy and possible differences in platelet biology. Data about platelet reactivity levels in females versus males presenting with STEMI is scarce. Purpose: Investigation of gender-driven variances in platelet reactivity and bleeding outcomes in STEMI patients planned to undergo pPCI. Methods: The COMPARE CRUSH trial was a randomized multicenter ambulance trial assessing the effect of prehospital administration of P2Y12 inhibitor loading dose with crushed versus integral prasugrel tablets in STEMI patients. We assessed the occurrence of high platelet reactivity (HPR), predictors of HPR at baseline and bleeding outcomes between females and males. Blood samples were analyzed at four prespecified time points using VerifyNow. Results: The COMPARE CRUSH trial included 633 STEMI patients in the period between November 2017 and March 2020. Females more frequently exhibited HPR at baseline than males (76% vs. 41%, odds ratio (OR), 4.58 [95% CI, 2.52 to 8.32], p<0.01). Moreover, female sex was a strong, independent predictor for HPR at baseline (OR, 4.93 [95% CI, 2.30 to 10.57], p<0.01). HPR rates at other time points were not significantly different between females and males. The risk of bleeding within the first 48 hours was significantly increased in females (OR, 6.02 [95% CI, 2.58 to 14.08], p<0.01), but after adjustment for baseline characteristics this increased risk was no longer statistically significant (OR, 2.61 [95% CI, 0.73 to 9.32], p=0.14). Conclusion: Female sex is an independent predictor for occurrence of HPR at baseline in STEMI patients. However, females exhibit a stronger platelet inhibition effect by oral P2Y12 inhibitors than males, which may contribute to an increased bleeding risk. A more tailored antiplatelet therapy approach should be considered for female STEMI patients to reduce bleeding risk. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): Unrestricted grants from Daiichi-Sankyo and Shanghai MicroPort Medical.